β-Arrestin1 and β-Arrestin2 Are Required to Support the Activity of the CXCL12/HMGB1 Heterocomplex on CXCR4 - D’Agostino, Gianluca; Artinger, Marc; Locati, Massimo; Perez, Laurent; Legler, Daniel F.; Bianchi, Marco E.; Rüegg, Curzio; Thelen, Marcus; Marchese, Adriano; Rocchi, Marco B. L.; Cecchinato, Valentina; Uguccioni, Mariagrazia (Frontiers in Immunology, 2020)
The chemokine receptor CXCR4 plays a fundamental role in homeostasis and pathology by orchestrating recruitment and positioning of immune cells, under the guidance of a CXCL12 gradient. The ability of chemokines to form heterocomplexes, enhancing their function, represents an additional level of regulation on their cognate receptors. In particular, the multi-faceted activity of the heterocomplex formed between CXCL12 and the alarmin HMGB1 is emerging as an unexpected player able to modulate a variety of cell responses, spanning from tissue regeneration to chronic inflammation. Nowadays, little is known on the selective signaling pathways activated when CXCR4 is triggered by the CXCL12/HMGB1 heterocomplex. In the present work, we demonstrate that this heterocomplex acts as a CXCR4 balanced agonist, activating both G protein and β-arrestins-mediated signaling pathways to sustain chemotaxis. We generated β-arrestins knock out HeLa cells by CRISPR/Cas9 technology and show that the CXCL12/HMGB1 heterocomplex-mediated actin polymerization is primarily β arrestin1 dependent, while chemotaxis requires both β arrestin1 and β arrestin2. Triggering of CXCR4 with the CXCL12/HMGB1 heterocomplex leads to an unexpected receptor retention on the cell surface, which depends on β-arrestin2. In conclusion, the CXCL12/HMGB1 heterocomplex engages the β arrestin proteins differently from CXCL12, promoting a prompt availability of CXCR4 on the cell surface, and enhancing directional cell migration. These data unveil the signaling induced by the CXCL12/HMGB1 heterocomplex in view of identifying biased CXCR4 antagonists or agonists targeting the variety of functions it exerts.